2017
DOI: 10.4103/ijd.ijd_321_16
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 17 mutations in four families from India with pachyonychia congenita

Abstract: Pachyonychia congenita (PC) is a rare autosomal dominant genetic skin disorder due to a mutation in any one of the five keratin genes, KRT6A, KRT6B, KRT6C, KRT16, or KRT17. The main features are palmoplantar keratoderma, plantar pain, and nail dystrophy. Cysts of various types, follicular hyperkeratosis, oral leukokeratosis, hyperhidrosis, and natal teeth may also be present. Four unrelated Indian families presented with a clinical diagnosis of PC. This was confirmed by genetic testing; mutations in KRT17 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…KRT17 is a multifunctional protein and is involved in the regulation of cellular processes, including proliferation, differentiation and inflammation (15). Increasing evidence has suggested that mutations in KRT17 are associated with pachyonychia congenita type 2 (16)(17)(18) and steatocystoma multiplex (19).…”
Section: Introductionmentioning
confidence: 99%
“…KRT17 is a multifunctional protein and is involved in the regulation of cellular processes, including proliferation, differentiation and inflammation (15). Increasing evidence has suggested that mutations in KRT17 are associated with pachyonychia congenita type 2 (16)(17)(18) and steatocystoma multiplex (19).…”
Section: Introductionmentioning
confidence: 99%
“…Within the rod domain, the heptad repeat‐containing segments coils 1A (84–120), 1B (139–230) and 2 (251–392) are interrupted by linker sequences . Genetic mutation in KRT17 that encodes K17 is related to tissue‐specific diseases, represented by steatocystoma multiplex (SM) and pachyonychia congenita (PC) .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nail discolorations, the nail color may indicate a secondary nail condition such as onychomycosis (yellow/brown), pseudomonas nail infection (green), or subungual hematoma (dark/brown/black). Nail clippings with histopathology, bacterial cultures, and fungal cultures may be used to diagnose other secondary nail conditions that may be contributing to the discoloration and symptoms, with appropriate treatment prescribed to alleviate these signs and symptoms [56, 57]. Over half of patients reported at least some psychological distress across the different gene groups, and most patients reported negative experiences during childhood and adolescence.…”
Section: Discussion/conclusionmentioning
confidence: 99%